High-Resolution Microendoscopy for the Detection of Cervical Neoplasia in Low-Resource Settings - Quinn, Mary K. (Public Library of Science, 2012)
Cervical cancer is the second leading cause of cancer death among women in developing countries. Developing countries often lack infrastructure, cytotechnologists, and pathologists necessary to implement current screening tools. Due to their low cost and ease of interpretation at the point-of-care, optical imaging technologies may serve as an appropriate solution for cervical cancer screening in low resource settings. We have developed a high-resolution optical imaging system, the High Resolution Microendoscope (HRME), which can be used to interrogate clinically suspicious areas with subcellular spatial resolution, revealing changes in nuclear to cytoplasmic area ratio. In this pilot study carried out at the women's clinic of Princess Marina Hospital in Botswana, 52 unique sites were imaged in 26 patients, and the results were compared to histopathology as a reference standard. Quantitative high resolution imaging achieved a sensitivity and specificity of 86% and 87%, respectively, in differentiating neoplastic (≥CIN 2) tissue from non-neoplastic tissue. These results suggest the potential promise of HRME to assist in the detection of cervical neoplasia in low-resource settings.